1986
DOI: 10.1136/bmj.293.6560.1459
|View full text |Cite
|
Sign up to set email alerts
|

Persistent HIV antigenaemia and decline of HIV core antibodies associated with transition to AIDS.

Abstract: Sequential serum samples from 13 homosexual men who seroconverted for antibodies to human immunodeficiency virus (HIV) were tested for HIV antigen. In one of these men, who developed the acquired immune deficiency syndrome (AIDS), HIV antigenaemia preceded the onset of AIDS by more than a year and persisted throughout the course of the disease. This antigenaemia was accompanied by the disappearance of IgG antibody reactivity to the major HIV core protein p24. In none of the 12 others, who all remained without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
98
0
3

Year Published

1988
1988
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(111 citation statements)
references
References 19 publications
8
98
0
3
Order By: Relevance
“…Antibody titres reached their maxima before anti-gp41 antibodies reached their highest avidity, thus limiting their ability to differentiate between recent and remote HIV infection. Our finding that once a maximum anti-gp41 titre has been achieved, like the anti-gp41 high avidity, it is maintained is in agreement with published work [31,32].…”
Section: Discussionsupporting
confidence: 93%
“…Antibody titres reached their maxima before anti-gp41 antibodies reached their highest avidity, thus limiting their ability to differentiate between recent and remote HIV infection. Our finding that once a maximum anti-gp41 titre has been achieved, like the anti-gp41 high avidity, it is maintained is in agreement with published work [31,32].…”
Section: Discussionsupporting
confidence: 93%
“…Recently, attention has been paid to the core antigens (gag) because of the low rate of mutation in the gag region and specific decreases in anti-gag antibodies before the development of AIDS in HIV-infected patients (19,34,43). Moreover, cellular immunity against viral core antigens is known to play a definitive role in recovery from viral infections (24,40,47), and several reports have indicated that cellular immunity against gag proteins was detectable in HIV infection (26,30,31,41,42).…”
mentioning
confidence: 99%
“…Very early on during his scientific career, as part of his Ph.D. thesis he demonstrated that individuals with higher levels of the HIV protein p24 were more likely to experience more rapid HIV disease progression, while long-term survivors had reduced p24 antigen in their blood. This discovery supported the concept of the use of antiretroviral therapy to reduce p24 antigen already during clinically asymptomatic infection and thereby prevent the onset of AIDS [1]. The p24 antigen test was later replaced by the more sensitive and accurate tests for measuring HIV RNA which remains the hallmark for assessing the success of treatment.…”
Section: © Marjolein Annegarnmentioning
confidence: 86%